PENGGUNAAN PERANTI KOHESI DAN KOHERENSI PADA NASKAH DRAMA KARANGAN SISWA KELAS VIII SMPN 7 KOTA BENGKULU - Dio Aristama; Rokhmat Basuki; Bambang Djunaidi (Jurnal Korpus, 2018)
The purpose of this study is to see and describe how the use of cohesion and coherency tools in the drama text of students of class VIII SMPN 7 Kota Bengkulu. The method used in this research is descriptive qualitative method. The data in this research is in the form of drama written by students. The source of this research data is the inter-faith dialogue in the student's drama script. Technique of collecting data using documentation method. Data analysis technique in this research is done through steps. Test the validity of the data used is credibility test  done by increasing persistence, supervisors during the process of guidance takes place, and discussion with colleagues. The result of the research is found that the cohesion device contained in the student's drama script is pronoun (pronoun) consisting of (1) the first single person pronoun who is saya, and Aku (2) the first person plural pronomina kami, and kita, (3) The second individual pronoun is kamu, and kau (4) the pronoun of your second plural, (5) the singular third person pronoun dia, (6) the third person's plural pronouns they are, (7) the guidance pronoun there, that, and this, (8) The pronouns are mu, ku, and dia. (9) Substitution devices are so, that, that, and the same. (10) The ellipsis device contains the removed part. (11) The conjunction device consists of the adversative conjunction that is but, the casual conjunction that is because, the coordinating conjunction adalah and / or, the subordinate conjunction is that, if, the correlative conjunction is either / or, the temporal conjunction is before. (12) Lexical devices consist of repetition (repetition) following the race, synonyms or maternal / parent, antonym or friendlike and hostile counterparts. There are ten types of means of coherence in the student's drama text are: (1) Coherence means of addition, and, also, (2) Coherence means of repetition or repetition of speech, (3) Coherence means of contrast or contradiction ie but (4) Coherence means (5) Coherence means the result or conclusion is so, (7) Synonym or synonyms coefficient of the word mother / parent, (8) Coherence of suppression means that even , (9) The means of coherence of causal relations is due, and (10) The time coherence means is that time. With the intensity of the use of means of coherence different from each other.Keywords: cohesion, coherence, drama by student essay